Multivariate analysis of tissues Raman spectra using regression methods - Lykina, A A; Artemyev, D N; Kukushkin, V I; Bratchenko, I A; Avraamova, S T; Aleksandrov, N S (Journal of physics. Conference series, 2019)
This work is devoted to the study of intact and tumor kidney tissues spectral properties. 532 nm, 785 nm, and 1064 nm lasers were used to stimulate Raman spectra and autofluorescence. Visually and morphologically unchanged tissues of human kidneys as well as tumor tissue were examined. Raman spectra have specific spectral markers for each tested subject. The analysis of the spectral characteristics was carried out with using projection on latent structures method to highlight the spectral features between the tissues.